The powerbend distribution provides a unified model for the species abundance distribution across animals, plants and microbes - Yingnan Gao; Ahmed Abdullah; Martin Wu (Nature Communications)
Abstract Remarkably, almost every ecological community investigated to date is composed of many rare species and a few abundant species. While the precise nature of this species abundance distribution is believed to reflect fundamental ecological principles underlying community assembly, ecologists have yet to identify a single model that comprehensively explains all species abundance distributions. Recent studies using large datasets have suggested that the logseries distribution best describes animal and plant communities, while the Poisson lognormal distribution is the best model for microbes, thereby challenging the notion of a unifying species abundance distribution model across the tree of life. Here, using a large dataset of ~30,000 globally distributed communities spanning animals, plants and microbes from diverse environments, we show that the powerbend distribution, predicted by a maximum information entropy-based theory of ecology, emerges as a unifying model that accurately captures species abundance distributions of all life forms, habitats and abundance scales. Our findings challenge the notion of pure neutrality, suggesting instead that community assembly is driven by a combination of random fluctuations and deterministic mechanisms shaped by interspecific trait variation.